2013
DOI: 10.1007/s00424-013-1417-7
|View full text |Cite
|
Sign up to set email alerts
|

MYBPC3's alternate ending: consequences and therapeutic implications of a highly prevalent 25 bp deletion mutation

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common form of inherited cardiac disease and the leading cause of sudden cardiac death in young people. HCM is caused by mutations in genes encoding contractile proteins. Cardiac myosin binding protein-C (cMyBP-C) is a thick filament contractile protein that regulates sarcomere organization and cardiac contractility. About 200 different mutations in the cMyBP-C gene (MYBPC3) have thus far been reported as causing HCM. Among them, a 25 base pair deletion in the bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Heterozygous carriers of these mutations often have incomplete penetrance and variable onset of disease [19], suggesting that other genetic or environmental factors modify the phenotype and influence the development of disease [20]. This view has been supported by studies of models of HCM-causing mutations in MYBPC3 and other genes that have been shown to be altered by genetic modifiers [20-22] and external stress [23], contributing to dysfunction and affecting the course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous carriers of these mutations often have incomplete penetrance and variable onset of disease [19], suggesting that other genetic or environmental factors modify the phenotype and influence the development of disease [20]. This view has been supported by studies of models of HCM-causing mutations in MYBPC3 and other genes that have been shown to be altered by genetic modifiers [20-22] and external stress [23], contributing to dysfunction and affecting the course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adding this test to the existing diagnostic tool kit will allow the frequency and severity of this variant to be determined over time by studying clinical outcomes [28]. Importantly, since this MYBPC3 ΔInt32 variant is highly prevalent, large-scale clinical screening can determine if this variant is a direct cause of cardiomyopathies or is a risk allele that acts with other pathogenic variants, or environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13). Due to an ancient founder mutation, 4% of the population of India carries a truncating MYBPC3 mutation (14,15). The majority of cardiac MYBPC3 mutations are predicted to encode truncated proteins that lack portions of either the carboxyl myosin and/or titin binding domains (7,13).…”
mentioning
confidence: 99%